2013
DOI: 10.1298/jjpta.vol16_003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Improvement in Various Impairments by Exercise Interventions in Patients with Knee Osteoarthritis: A Systematic Review and Meta-analysis of Randomized Clinical Trials

Abstract: ABSTRACT. Purpose: To investigate improvement in various impairments by exercise interventions in patients with knee osteoarthritis (OA). Methods: We collected data on randomized controlled trials (RCTs) comparing the effects of exercise intervention with those of either nonintervention or psychoeducational intervention in patients with knee OA. Data on pain, stiffness, muscle strength, range of motion, fl exibility, maximal oxygen uptake, and position sense were synthesized. The Grading of Recommendations Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Effect sizes were large in the present study and were comparable to, or superior to, those seen in other trials conducted using non-pharmacological approaches in patients with knee osteoarthritis. 19,[32][33][34][35][36][37][38][39] Massage does not carry the adverse effects of many pharmacologic and invasive treatments. 6,7,12,40,41 While osteoarthritis treatment guidelines favor pharmacotherapy, 42 preferred treatments like NSAIDs and acetaminophen are frequently overused, increasing the risk of adverse effects such as gastrointestinal, cardiac, and renal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Effect sizes were large in the present study and were comparable to, or superior to, those seen in other trials conducted using non-pharmacological approaches in patients with knee osteoarthritis. 19,[32][33][34][35][36][37][38][39] Massage does not carry the adverse effects of many pharmacologic and invasive treatments. 6,7,12,40,41 While osteoarthritis treatment guidelines favor pharmacotherapy, 42 preferred treatments like NSAIDs and acetaminophen are frequently overused, increasing the risk of adverse effects such as gastrointestinal, cardiac, and renal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous postoperative interventions have been tested in different clinical settings designed to maximize recovery or functioning, alleviate pain, prevent joint stiffness and muscular atrophy, and improve mental capabilities and coordination [ 4 , 5 ]. Recently, two intervention types have grown in popularity: mindfulness-based cognitive therapy (MBCT) [ 6 ] and isometric exercise training (IET) interventions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…IET is performed by increasing muscle tension while preventing joint motion, most often by providing unmoving resistance during an exercise [ 11 ]. A meta-analysis/systematic review of 33 randomized controlled trials showed that exercise interventions can improve pain, stiffness, muscle strength, maximal oxygen uptake, and position sense (awareness) [ 7 ]. Previous research also shows that breast cancer patients who participated in a brief IET intervention showed alterations in tumor tissue gene expression [ 12 ], suggesting that exercise may have direct effects on biological mechanisms associated with cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the meta-analysis also reported that the exercise reduced the BP in pregnancy by 9%. Furthermore, the exercise prevented new episodes of sick leave due to lumbo-pelvic pain ( Tanaka et al., 2013 ).…”
mentioning
confidence: 99%